Application of multi-position method to calibration using optical coordinate measuring machines. (December 2021) - Krawczyk, M.; Kobiela, K.; Jedynak, M.; Harmatys, W.; Sładek, J.
Abstract: The study explores the potential applications of the multi-position method to calibration of optical standards of length and geometric characteristics using Optical Coordinate Measuring Systems (OCMS). The differences between contact and optical measurement in performing similar measurement procedures are presented. At the end of the document the procedure for validating the calibration method is outlined.